2022
DOI: 10.3389/fpsyt.2022.805851
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Microstructural Medial Prefrontal Cortex Changes Using Magnetic Resonance Imaging Texture Analysis in a Post-Traumatic Stress Disorder Rat Model

Abstract: BackgroundRadiomics is characterized by high-throughput extraction of texture features from medical images and the mining of information that can potentially be used to define neuroimaging markers in many neurological or psychiatric diseases. However, there have been few studies concerning MRI radiomics in post-traumatic stress disorder (PTSD). The study's aims were to appraise changes in microstructure of the medial prefrontal cortex (mPFC) in a PTSD animal model, specifically single-prolonged stress (SPS) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Previously, we used stepwise discriminant analysis (SDA) and LASSO regression methods to screen mPFC texture features based on T2W images and build radiomics classi cation models for rats in the control and PTSD groups [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we used stepwise discriminant analysis (SDA) and LASSO regression methods to screen mPFC texture features based on T2W images and build radiomics classi cation models for rats in the control and PTSD groups [33] .…”
Section: Discussionmentioning
confidence: 99%
“…MRI showed hippocampal volume reduction, decreased local blood ow, reduced N-acetylaspartate content, and abnormal activity in patients with PTSD [31,32] . In our previous study [33] , we used medial prefrontal cortex (mPFC) T2W image texture analysis to classify PTSD rats and found that changes in mPFC texture feature parameters in PTSD rats may be associated with abnormalities in nuclei, neurons, and glial cells. The texture analysis showed good classi cation performance.…”
Section: Introductionmentioning
confidence: 99%